USING “UNFINISHED STORY” TO IMPROVE STUDENTS’ WRITING ABILITY OF THE FIRST GRADE OF ENGLISH EDUCATION PROGRAM OF STKIP HAMZANWADI SELONG - Wati, Laila (Universitas Hamzanwadi, 2012)
This research was designed to improve the students’ writing narrative text in English through unfinished story. A collaborative action research design was employed, involving the researcher and a collaborator.The design applied in this research was a classroom action research. Data in the form of observation checklist and students’ writing product were collected at the end of the cycle then analysed qualitatively and quantitatively. The success was determined from the improvement of the students’ score on their writing product. The findings respectively showed that the unfinished story improved the students’ writing ability. The improvement can be seen on the students’ individual writing scores. The findings also showed that this media was effective in enhancing the students’ involvement in the instructional activities. Key words: unfinished story, narrative text, writing ability